VIKOR method with Z-number approach for portfolio selection decision / Zamali Tarmudi ... [et al.] - Tarmudi, Zamali; Nahar Ahmad, Shamsatun; Mohammad, Siti Afiqah; Ghazali, Ahmad Faiz; Abd Rahman, Mazlyda; Triana, Yaya Sudarya (Universiti Teknologi MARA, 2024)
Investors and decision makers (DMs) have become increasingly interested in portfolio selection in a borderless world in recent years. In real-world market situations, the performance of a great number of portfolios is typically unpredictable due to the presence of uncertainty and unreliable factors in numerous criteria. Therefore, it is essential to increase investor returns and promote an investment strategy through thorough evaluation. This occurrence becomes critical if the DMs employ an unsuitable strategy that fails to handle both aspects in a prudent manner. Due to its importance, this paper implements a VIKOR method with a Z-number approach for selecting the optimal portfolio among the identified alternatives. It is believed that the two components A and B of the Z-number structure, where A is a restriction of the evaluated attribute and B is a degree of certainty of A, deal with uncertainties and reliability issues more effectively. A numerical example from an adopted case study has been provided to demonstrate the effectiveness and viability of the proposed method. The outcome demonstrates that the approach can address the uncertainty of human judgement with greater precision while simultaneously boosting the DMs' confidence throughout the evaluation process. Consequently, the proposed method provides a more dependable and effective method for DMs to make decisions, particularly regarding portfolio selection.